2020
DOI: 10.31501/rbpe.v10i3.11811
|View full text |Cite
|
Sign up to set email alerts
|

Motivação em pilotos de motovelocidade

Abstract: A motivação é um processo ativo dirigido a uma meta que sofre influências psicológicas e fisiológicas, despertadas a partir de determinantes ambientais e/ou pessoais. Sendo assim, o objetivo desta pesquisa foi verificar os níveis motivacionais e a relação com a idade e o tempo de prática em pilotos de motovelocidade. Participaram 38 praticantes amadores de motovelocidade, adultos, do sexo masculino, independente da categoria e nível de pilotagem. Aplicou-se a Escala de Motivação para o Esporte II antes da bate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We found few national studies that used SMS-II to assess the motivation of Brazilian sports practitioners and when they did, it was not reported the measures of internal consistency of the instrument 13,14 . Others Brazilian studies reported general Cronbach's Alpha of the instrument and did not show the reliability for each scale 15,16 .…”
Section: Introductionmentioning
confidence: 98%
“…We found few national studies that used SMS-II to assess the motivation of Brazilian sports practitioners and when they did, it was not reported the measures of internal consistency of the instrument 13,14 . Others Brazilian studies reported general Cronbach's Alpha of the instrument and did not show the reliability for each scale 15,16 .…”
Section: Introductionmentioning
confidence: 98%